Exploring Lived Experience: The Integration of AI in Junior & Senior High Schools in Bandung - Supriadi, Alfian; Sururi; Nurdin (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2025)
This study purpose to explore the lived experiences of students, teachers, and parents regarding the integration of Artificial Intelligence (AI) in junior and senior high school education across three model schools in Bandung, Indonesia. Employing a qualitative narrative inquiry design, data were collected through in-depth interviews with eight informants representing public, religious, and vocational school settings. The findings reveal that AI is experienced as a formative mirror, offering real-time feedback and encouraging skill development, but also evokes emotional contradictions, including anxiety, perfectionism, and spiritual dissonance. Teachers and parents were found to be essential mediators who reframed AI’s presence through relational, ethical, and religious frameworks. In faith-based contexts, participants expressed concern over AI’s inability to capture sincerity (niat) or foster moral reflection, underscoring its epistemological and spiritual limits. The study concludes that AI must be integrated through a culturally responsive, ethically anchored approach that balances digital efficiency with human meaning, emotional resonance, and pedagogical intentionality.